MECHANISMS OF STATE REGULATION OF THE REAL ESTATE MARKET IN CONDITIONS OF DECENTRALIZATION - Suray, Inna; Hoi, Nataliia; Matiichyk, Andrii (Public Management and Policy, 2025)
In the context of ongoing decentralization processes, the real estate market in Ukraine is a key indicator of economic activity and a vital tool for shaping the financial foundation of local development. Deepening regional autonomy in land management, urban planning policy and tax administration creates new opportunities for attracting investment, but at the same time it generates risks of fragmentation of the regulatory environment. Analysis of mechanisms of state regulation of the real estate market, taking into account regional specifics and international experience, allows us to identify areas for increasing the effectiveness of policy in this area. The purpose of the study is to assess the current state and trends in the development of the real estate market of Ukraine in the context of decentralization, to identify problems and disparities in regulation at the local and national levels. The methodological basis of the study is the systemic and structural-functional approaches, economic and statistical analysis, methods of comparative analysis, as well as content analysis of regulatory acts and strategic documents. The study showed that the Ukrainian real estate market in 2025 is characterized by an increase in capitalization (USD 667.4 billion) and significant regional differentiation. Western regions (Lviv, Ternopil, Ivano-Frankivsk) demonstrate a steady growth in prices and demand, central regions maintain stable positions, while eastern and southern regions have limited development due to security risks. Key problems were identified: fragmentation of the legal field, low integration of cadastral and registration data, and uneven institutional capacity of local authorities, which reduces the effectiveness of regulation. Foreign experience confirms the effectiveness of combining local flexibility with national standards of transparency, security and administration, the introduction of electronic platforms, as well as financial equalization mechanisms. The proposed areas for improving state regulation mechanisms include: creating a single integrated electronic system of cadastral and registration data; increasing the transparency of transactions through electronic auctions and open registers; improving tax administration in the real estate sector.